Does money have a role in the inflation process? Evidence from Australia. (8th November 2018) - Hossain, Akhand Akhtar
Abstract : Inflation, defined as a sustained increase in the price level, is considered a monetary phenomenon, as it can be explained within the framework of money‐demand and money‐supply relationships. In the extant literature, money growth is shown to remain causally related to inflation across countries and over time, irrespective of the exchange rate regime and stability of the money‐demand function. Nevertheless, emerging literature suggests a diminishing role of money in the conduct of monetary policy for price stability, especially under inflation targeting. Monetary policy in Australia under inflation targeting since 1993 is an example of policy that denies a relationship between money growth and inflation. The proposition that money does not matter insofar as inflation is concerned seems odd in both theory and the best‐practice monetary policy for price stability. This paper uses annual data for the period 1970–2017 and quarterly data for the period 1970Q1–2015Q1. It deploys both the Johansen cointegration approach and the autoregressive distributed lag (ARDL) cointegration approach to investigate for Australia whether money, real output, prices and the exchange rate (non‐stationary variables) maintain the long‐run price‐level relationship that the classical monetary theory suggests in the presence of such stationary variables as the domestic and foreign interest rates. As expected, the empirical findings for Australia are consistent with the classical long‐run price‐level relationship between money, real output, prices and the exchange rate. The error‐correction model of inflation confirms the presence of a cointegral relationship among these variables; it also provides strong evidence of a short‐run causal relationship between money supply growth and inflation. On the basis of a priori theoretical predictions and empirical findings, the paper draws the conclusion that the monetary aggregate and its growth rate matter insofar as inflation is concerned, irrespective of the strategy of monetary policy for price stability.